STUDENTS’ COMMUNICATION SKILLS AND EMOTIONAL INTELLIGENCE TO DEVELOP THE IMPLEMENTATION OF HOTEL SUPERVISION MANAGEMENT: MEDIATION ROLE OF DIGITAL LITERACY - Antonius Iskandar Yahya (LPSDI Bina Patria, 2024)
Effective implementation of hotel supervision management is crucial for students in tourism and hospitality management programs to meet the operational demands of modern hotels. This study aims to explore the effects of Communication Skills and Emotional Intelligence on the Implementation of Hotel Supervision Management, with a focus on the mediating role of Digital Literacy. A quantitative approach was used, employing a survey questionnaire administered to 150 students who had completed apprenticeships or practical training in hotel management. Data were analyzed using descriptive statistics and structural equation modeling (SEM) with Partial Least Squares (PLS). The findings reveal that both Communication Skills and Emotional Intelligence significantly influence hotel supervision management implementation, with Digital Literacy serving as a key mediator. The study introduces novel insights into the integration of digital competencies in supervisory roles, providing practical implications for enhancing training programs in hospitality education